PERMODELAN KONSTRUKSI RUMOH ACEH MENGGUNAKAN BAJA SEBAGAI MATERIAL ALTERNATIF - Nurul Fathiyyah; Yunita Idris; Huzaim Huzaim (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
Rumoh Aceh is believed have high capacity and safe under seismic loads. This is due to the main construction of Rumoh Aceh is timber construction. Timber is a relative safe material in the seismic prone zone area because it is not as rigid as concrete. Steel is also believed a safe material of construction in high risk earthquake area. In this article, modelling Rumoh Aceh that constructed using steel and analyse its behaviour under seismic load is presented. The model used the 208,84 m2 of Rumoh Aceh with circular timber columns (D20 cm) and size of the beams is 6,5/25 cm. The size of the construction is archetype of the majority traditional houses. The house construction then remodelled with a circullar hollow steel for the columns (165,2 x 4.5 mm) and WF 175 x 125 x 5,5 x 8 mm, and WF 125 x 125 x 6,5 x 9 mm for the main and secondary beams. The behaviour of the construction under seismic excitation is analysed by response spectrum methods using the structural analysis software, i.e. SAP2000. Based on the results of the analysis, both of the construction meet the requirement of earthquake standard for each material standard (SNI 7973:2013 and SNI 1729:2020). Comparing structural behavior is obtained in both qualified modeling based on SNI 1726:2019. However, the timber construction perform higher displacements, drifts, and base shears.